Investigating EFL Learner Needs of English for Hospitality Subject in Vocational School - Firdaus , Moch. Malik Al; Yuliasri , Issy; Rukmini , Dwi; Pratama , Hendi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
With the growing demands of the hospitality industry, English proficiency is becoming essential for workers to succeed. As the industry expands, vocational high school students in hotel management programs are eager to join the professional field. However, a recent study shows there is not an English course specifically tailored to their needs in hospitality, despite the curriculum’s recommendations to use student-focused materials. This research, therefore, is designed as a needs analysis, an important first step in developing English for Specific Purposes (ESP) courses, as outlined by Brown (2016). The study examines students' current English abilities in hospitality (Present Situation Analysis), compares them to industry requirements (Target Situation Analysis), identifies gaps, and explores student preferences for learning (Individual Differences and Classroom Learning Analysis). Findings indicate that hospitality students aim to improve their English skills, particularly in listening and speaking for front office, restaurant service, and housekeeping scenarios. However, their current proficiency falls short of meeting industry expectations in two of these three areas. Students also expressed preferences for task-based learning, role-play activities, a hands-on approach, video content, and small-group learning. The data includes interview excerpts, allowing future researchers to consider responses that may differ from the majority. This needs analysis highlights key areas to focus on when designing ESP materials that truly support students in meeting the demands of the hospitality industry.